THE ROLE OF ORF1AB AND N GENES IN UNDERSTANDING THE SARS-COV-2 RNA SEQUENCE (Literature Review) - Sobirjon T. Jumamurodov; Zukhra A. Nuruzova (Central Asian Journal of Medicine, 2025)
Molecular diagnostic methods are widely used in the detection of the SARS-CoV-2 virus, in particular, real-time polymerase chain reaction (RT-PCR) technology is considered the gold standard for these purposes. Various genetic markers in the viral genome are used to identify them, of which the ORF1ab and N genes are the most important. These genes contain sequences that are specific to the virus, and by targeting them, SARS-CoV-2 RNA can be identified with high sensitivity and accuracy. The article is devoted to the analysis of the scientific literature and role of genes ORF1ab and N in molecular diagnostics.